PENGARUH PERBANDINGAN DOSIS PUPUK KANDANG TERNAK AYAM DAN SAPI TERHADAP BIOMASSA JAGUNG DAN DINAMIKA KATION TANAH - Indriani Indriani; Muhammad Helmy Abdillah; Nadia Aprilia Putri; Muhammad Rasidi Said; Roby Roby; Amelia Santi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Soil nutrient deficiency is a problem aftermath of reduction caused by metals and leaching due to low soil organic matter and high input of synthetic chemical fertilizers. The decline in the corn harvest index is a decrease in soil fertility. Hence, local organic materials have urgently needed as a Ultisol ameliorant. This study aims to determine the right combination of chicken manure and cow manure to produce the best increase in plant height and increase the plant dry weight, soil pH, and CEC. The research has conducted at the Hasnur Polytechnic, South Kalimantan, from April 2022 to August 2022 and used a completely randomized design with 200 g of manure divided into three combinations of P0 (control), P1 (30% chicken manure versus 70% cow manure), P2 (50% chicken manure versus 50% cow manure), P3 (70% chicken manure versus 30% cow manure). The results showed that the P2 treatment increased plant height, dry weight, and optimal soil pH, while P3 showed significant soil CEC because chicken manure had varied and balanced nutrient content compared to cow manure.